2021
DOI: 10.3389/fpsyt.2021.631420
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Caregiving Knowledge and Skills With Caregiver Burden, Psychological Well-Being, and Coping Styles Among Primary Family Caregivers of People Living With Schizophrenia in China

Abstract: Background: There is a lack of clarity regarding the correlation of caregiving knowledge and skills with caregiving experiences of people living with schizophrenia (PLSs). To address this gap, this comprehensive study examines the relationships of caregiving knowledge and skills to the primary family caregiver's experiences of burden, psychological well-being (stress, anxiety, depression, caregiving rewarding feelings), and coping styles in China.Methods: A total of 395 primary family caregivers of PLSs were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 81 publications
3
15
0
2
Order By: Relevance
“…Evidence regarding the relationship between well-being and HL seems to be an available heuristic area. However, the conclusions of this study are corroborated by a study from China, where caregivers’ knowledge and skills of people with schizophrenia were identified as a significant predictor of well-being [ 43 ]. However, a systematic review identified mixed findings associating internet-based support interventions for caregivers to positive outcomes on well-being for most of the sample, despite six of the studies included in the review reporting negative outcomes [ 44 ].…”
Section: Discussionsupporting
confidence: 76%
“…Evidence regarding the relationship between well-being and HL seems to be an available heuristic area. However, the conclusions of this study are corroborated by a study from China, where caregivers’ knowledge and skills of people with schizophrenia were identified as a significant predictor of well-being [ 43 ]. However, a systematic review identified mixed findings associating internet-based support interventions for caregivers to positive outcomes on well-being for most of the sample, despite six of the studies included in the review reporting negative outcomes [ 44 ].…”
Section: Discussionsupporting
confidence: 76%
“…SZ is considered a severe and complex mental illness characterized by positive and negative symptoms, including delusions, hallucinations, thought disorder, apathy, and avolition as well as cognitive and functional impairment. Reports have shown that SZ prevalence changes with age in an inverted U-shape, with the highest value at around 40 years and nearly 71% of total cases being aged 25-54 years ( Zhou et al., 2021 ). Due to SZ epidemiological characteristics, aging SZ patients are easy to ignore.…”
Section: Introductionmentioning
confidence: 99%
“…In other populations, nonpharmacological interventions have proven to be effective for family caregivers, including psychoeducation (Sin & Norman, 2013), mutual support programs (Chien & Norman, 2009), counseling (Shuler, 2014), and web-based or telephone interventions (Corry et al, 2019;Wilz et al, 2018). Caregiving knowledge and skills might influence the caregivers' psychological wellbeing (Zhou et al, 2021), meaning that controlled clinical trials in caregivers of individuals with mental disorders could be helpful for identifying means to reduce their mental health burden and thus indirectly improve the care they provide. Implementing these strategies is expensive and time-consuming, but they tend to be more effective than pharmacological treatment alone in managing psychological distress, burden and psychiatric symptoms in family caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…More support from mental health services could help caregivers to progress in their emotional trajectory towards coping and improve their caregiving knowledge and skills. This support could positively impact their quality of life, and thus improve the quality of life of the people they care for (Lima-Rodríguez et al, 2022;Zhou et al, 2021). Mental health nurses have a role in patients' and caregivers' education and in the promotion of psychological wellbeing.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation